Effects of shoe collar height and arch-support orthosis on joint stability and loading during landing - Lam, W.-K.; Cheung, C. C.; Huang, Z.; Leung, A. K. (Research in Sports Medicine, 2022)
This study examined the effects of shoe collar height and foot orthosis on ground reaction force (GRF), ankle and knee mechanics during landing. Sixteen male university basketball players performed drop landing when wearing different shoes with collar height (high vs. low) and foot orthoses (arch-support vs. flat). Biomechanical variables included vertical peak GRF and joint angles and moments in sagittal and coronal planes were analysed with two-way ANOVA with repeated measures (a=0.05). Results indicated that high-collar shoes had significantly smaller peak ankle dorsiflexion (P <0.001), smaller ankle sagittal total RoM (P <0.001), higher forefoot peak GRF (P =0.009) and peak knee valgus moment (P <0.001) compared with low-collar shoes. Wearing arch-support orthoses induced higher forefoot peak GRF (P <0.001) but smaller ankle inversion moment (P =0.001) compared to flat-orthoses. Furthermore, significant interactions between collar-height and orthosis were found only for initial ankle plantarflexion (P =0.023) and knee flexion (P =0.035), but not in any kinetics variables. The findings suggest increased collar height and arch-support orthoses appear to reduce the risks of ankle sprains during landing, but might increase loading at adjacent joints.